Assessing the habitat suitability of two different artificial wetland habitats using avian community structures - Hussin, Mohamed Zakaria; Rajpar, Muhammad Nawaz (Science Publications, 2014)
Artificial wetlands have become highly important habitat for a variety of bird species particularly waterbirds due to loss and degradation of natural wetlands. Avian community structures in two artificial wetland habitats i.e., man-made marsh and lake were investigated to identify the suitability of the habitats for avian species, habitat preference and food resources. Distance sampling point count method detected 35272 bird individuals of 98 species from July to November 2010. Ninty four bird species were recorded from man-made marsh and thirty one species from the lake area. Acridotheres tristis (6.34% of all detections) was the most dominant bird species of man-made marsh and Passer montanus (0.41%) was the most dominant bird species of lake habitat. On the contrarily, Microhierax fringillarius and Turdoides earlei (each 0.01%) were the rarest species of man-made marsh and Dinopium javanense (0.02%) was the rarest species of the lake habitat. The bird relative abundance of man-made marsh and lake habitats was significantly different (F1,194 = 50.3, p<0.05). Community analysis indicated that bird species of man-made marsh were more diverse i.e., Shannons index (N1 = 3.92) and rich i.e., Margalefs index (R1 = 8.93) than the lake habitat. Insectivore (marsh; 21.13% and lake area; 1.21%) was the most dominant guild in man-made marsh and lake area. In contrast, Piscivore (0.14%) was the rarest guild comprised of only one species in marsh habitat. The results of this study revealed that the man-made marsh was more capable to attract a higher number of bird species and diversity than the lake habitat.